2019
DOI: 10.3390/foods8090423
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Chitosan/Corn Starch/Cinnamaldehyde Films for Strawberry Preservation

Abstract: In this study, the casting method was used to make chitosan (CS)/corn starch/cinnamaldehyde film, and the preservation performance of the film was examined. The results showed that the tensile strength of the film can reach to 31.24 ± 0.22 MPa when the mass ratios of CS, corn starch, and glycerin were 2.5%, 7%, and 0.5% respectively. The addition of cinnamaldehyde made the films have great inhibitory effect on Botrytis cinerea, Rhizopus, and Escherichia coli. In particular, the film had a significant fresh-kee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 47 publications
3
21
0
Order By: Relevance
“…Strawberries packed in cinnamaldehyde essential oils show similar results. 53 Our results indicated that coating films containing microcapsules of oregano essential oil and SA effectively slowed down the metabolism of freshly cut purple yam. The ascorbic acid content of purple yam is shown in Fig.…”
Section: Firmnessmentioning
confidence: 60%
“…Strawberries packed in cinnamaldehyde essential oils show similar results. 53 Our results indicated that coating films containing microcapsules of oregano essential oil and SA effectively slowed down the metabolism of freshly cut purple yam. The ascorbic acid content of purple yam is shown in Fig.…”
Section: Firmnessmentioning
confidence: 60%
“…Titratable acidity (TA) of the samples were assessed using a pH-meter and a titration of each sample was performed with 0.1 M NaOH to an end point of 8.2 and the results were expressed as gr of citric acid per 100 g of sample. In addition, the L-ascorbic acid concentration in homogenized blended strawberries was determined by redox titration using iodine solution and expressed as ascorbic acid content in 100 g of sample [10,36,37].…”
Section: Physical and Chemical Properties Of Strawberriesmentioning
confidence: 99%
“…Chitosan was already involved in this goal where films with different molecular weight and chitosan/corn amylose/cinnamaldehyde films were used for the packaging strawberries to extend their shelf life [35]. In addition, strawberries were dipped in different aqueous solutions like CaCl2 or salicylic acid (SA) in different concentrations, solution of N-succinyl chitosan (NSC) immobilized on lysozyme and sodium alginate solution combined with ZnO NPs were applied as an edible coating to increase the shelf life of post-harvest [36][37][38][39]. Also, techniques such as atmospheric cold plasma (ACP) and electrostatic spraying (ES) were used as efficient techniques for strawberry preservation [20,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…1 As high-activity biomass compounds, they are widely used in the chemical, medicine, and food industry due to their strong ability of sterilization and antisepsis. [2][3][4][5] Given their structural similarity, the four compounds are regarded as 3-phenyl-2-propene compounds with bifunctional groups. Owing to the unsaturated carbon-carbon double bonds, the four 3-phenyl-2-propene compounds were oxidized easily to aldehyde and epoxy derivatives, resulting in limited application.…”
Section: Introductionmentioning
confidence: 99%